ACTB Methylation in Blood as a Potential Marker for the Pre-clinical Detection of Stroke: A Prospective Nested Case-Control Study - Liu, Chunlan; Yin, Qiming; Li, Mengxia; Fan, Yao; Shen, Chong; Yang, Rongxi (Frontiers in Neuroscience, 2021)
Background: Stroke is the second leading cause of death worldwide. If the risk of stroke could be evaluated early or even at a preclinical stage, the mortality rate could be reduced dramatically. However, the identified genetic factors only account for 5% to 10% of the risk of stroke. Studies on the risk factors of stroke are urgently needed. We investigated the correlation between blood-based β-actin (ACTB) methylation and the risk of stroke in a prospective nested case-control study. Methods: The methylation level of ACTB was quantitatively determined by mass spectrometry in 139 stroke cases who developed stroke within 2 years after recruitment and 147 age- and sex-matched controls who remained stroke-free in a median follow-up of 2.71 years. Results: We observed a highly significant correlation between hypomethylation of one CpG site of ACTB and increased risk of stroke in an onset-time-dependent manner (for onset time ≤ 1.5 years: odds ratio (OR) per +10% methylation = 0.76, P = 0.001; for onset time ≤ 1.32 years: OR per +10% methylation = 0.59, P = 7.82x10-7; for onset time ≤ 1 year: OR per +10% methylation = 0.43, P = 3.00x10-6), and the increased cumulative incidence of stroke (log-rank P = 3.13x10-7). Neighboring CpG sites showed an inverse correlation with age and drinking status in controls (P < 0.05) but not in stroke cases. Conclusion: we firstly reported the blood-based ACTB methylation as a marker for the risk evaluation and preclinical detection of stroke, which can be further modified by age and drinking.